(untitled) (Journal of Global Accounting, 2023)
This study focused on audit quality on earnings management of listed Nigerian pharmaceutical companies with the following objectives: To examine the effect of audit firm size on discretionary accrual of listed Pharmaceutical companies in Nigeria; to assess the effect of audit tenure on discretionary accrual of listed Pharmaceutical companies in Nigeria; to ascertain the effect of audit fee on discretionary accrual of listed Pharmaceutical companies in Nigeria; to evaluate the effect of audit firm specialization on discretionary accrual of listed Pharmaceutical companies in Nigeria.. A total of seven pharmaceutical companies listed on the floor of the Nigerian Exchange (NGX) Group as at 31st December 2021 were sampled. The data were sourced from publications of the Nigerian stock exchange (NSE), fact books and the annual report and accounts of the sampled pharmaceutical companies. Pearson correlation coefficient and panel least square (PLS) regression were used for analysis of the pharmaceutical companies for the years 2010 – 2021. Based on the analyzed results, the following summary of findings was provided: audit firm tenure has a significant but positive effect on discretionary accrual of listed pharmaceutical companies in Nigeria at 5% level of significance while audit firm size, audit fee and audit firm specialization has a significant but negative effect on discretionary accrual of listed pharmaceutical companies in Nigeria at 5% level of significance. This study concluded that; Audit Firm Size has a significant but negative effect on Discretionary Accrual; Audit Tenure has a significant and positive effect on Discretionary Accrual; Audit Fee has a significant but negative effect on Discretionary Accrual; Audit Firm Specialization has a significant but negative effect on Discretionary Accrual of listed Pharmaceutical companies in Nigeria at 5% level of significance. The following recommendations were made: that firms should always consider competence and experience of the audit firms rather than size that are likely to be associated with less earnings management of firms; accounting professional bodies should strictly ensure that their members who audit for their clients do not audit for more than three years at a spring to sphere the independence of the auditor and his/her objectivity; firms should find ways to lower audit cost by negotiating the audit services to be assessed in rates and hours, not just total fee level; that Auditors should have knowledge not only in auditing and accounting but also on clients’ industry to deliver higher quality audit services than one audited by non-specialized auditor.